Time-Travelling Feminism: Yogmaya’s Legacy and the Rewriting of Feminist Praxis in Nepal - Katuwal, Saraswati (NPRC Journal of Multidisciplinary Research, 2025)
This article reinterprets the legacy of Yogmaya Neupane (1860–1941) through a South Asian feminist lens, arguing that her activism exemplifies “time-travelling feminism.” Her poetic baani, critique of caste and gender hierarchies, and climactic protest against the Rana regime reveal a radical feminist praxis that unsettles patriarchal and state authority. Rather than situating her as a saintly reformer, the study frames Yogmaya as a subaltern feminist theorist whose praxis transcends linear histories of feminist progress. Drawing on Gayatri Chakravorty Spivak’s subalternity, Chandra Talpade Mohanty’s contextual feminism, Sharmila Rege’s testimonial epistemologies, Uma Chakravarti’s Brahmanical patriarchy, and Srila Roy’s postsecular feminist agency, it positions Yogmaya as a political ancestor whose dissent continues to shape feminist struggles in Nepal today. The analysis shows how her insurgent spirituality resonates with Dalit, Janajati, and Madhesi women’s movements, offering an indigenous grammar of resistance that challenges Eurocentric feminist paradigms.